ANALYSIS METHOD OF TRANSFER PRICING USED BY MULTINATIONAL COMPANIES RELATED TO TAX AVOIDANCE AND ITS CONSISTENCIES TO THE ARM’S LENGTH PRINCIPLE (CASE STUDY: STARBUCKS CORPORATION) - Sari, Nuraini; Hunar, Ririn Susanti (Bina Nusantara University, 2015)
The purpose of this study is to evaluate about how Starbucks Corporation uses transfer pricing to minimize the tax bill. In addition, the study also will evaluate how Indonesia’s domestic rules can overcome the case if Starbucks UK case happened in Indonesia. There are three steps conducted in this study. First, using information provided by UK HMRC and other related articles, find methods used by Starbucks UK to minimize the tax bill. Second, find OECD view point regarding Starbucks Corporation cases. Third, analyze how Indonesia’s transfer pricing rules will work if Starbucks UK’s cases happened in Indonesia. The results showed that there were three inter-company transactions that helped Starbucks UK to minimize the tax bill, such as coffee costs, royalty on intangible property, and interest on inter-company loans. Through a study of OECD’s BEPS action plans, the authors recommends to improve the OECD Model Tax Convention including Indonesia’s domestic tax rules in order to produce a fair and transparent judgment on transfer pricing. This study concluded that by using current tax rules, although UK HMRC has been disadvantaged because transfer pricing practices done by most of multinational companies, UK HMRC still cannot prove the transfer pricing practices are not consistent with arm’s length principle. Therefore, current international tax rules need to be improved.